Some problematical arthropods from the Upper Ordovician Letna Formation of Bohemia - Chlupac,I. (Journal of the Czech Geological Society, 1999)
The description of so far incompletely known enigmatic arthropods Zonozoe drabowiensis Barrande, 1872, Furca bohemica Fritsch, 1908, F. pilosa sp. n. and Nothozoe pollens Barrande, 1872 is presented or supplemented. The new genus Zonoscutum n. gen. with Z. solum sp. n. as the type species is established and remnants of a giant arthropod (possibly eurypterid) are reported in the open nomenclature. All material derives from the Letna Formation (lower Berounian, Upper Ordovician) of the Barrandian area, Czech Republic.
Keywords: Arthropoda incertae sedis; Upper Ordovician; Barrandian area; Czech Republic